Effectiveness of Psychoeducation Techniques and Guidance Counseling Services for Non-Guidance Counseling Primary Teachers - Hasna Hafizhah Salma (Bina Nusantara University, 2023)
There is still limited availability of primary level school counselors, even though they play a significant role in helping primary level students grow and develop academically, socially, and emotionally. However, non-counseling teachers, such as homeroom teachers, religion teachers, and teachers of other subjects, also carry out the role of school counselors. Unfortunately, most of these teachers do not understand their ability to provide optimal counseling services. Therefore, this research aims to determine the effectiveness of psychoeducation in improving the understanding of non-counseling teachers regarding counseling guidance techniques and services. This quasi-experimental research with a one-group pre-test post-test design was conducted with 38 subjects selected using purposive sampling. The data analysis used the 1-tailed Wilcoxon test with JASP version 0.18.0. The results show that psychoeducation is effective in improving the understanding of counseling techniques and services among non-counseling teachers. The implications of this study can be useful for teachers, policymakers, and future researchers.